Implementasi Media Tajwid Putar dalam Pembelajaran Ilmu Tajwid - Yesi Fadlilah; Zainal Abidin (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
Studying Tajwid (science of reciting the Koran) is the fardlu kifāyah, but practicing it in reciting the Koran is fardlu ‘ain, so Tajwid has been taught to Muslim children since they learned to recite the Koran. However, it has been considered to be very demanding and problematic. The conventional methods used tend to be uninteresting and boring. For that reason, a learning media that makes teachers and students is in an interactive, effective and joyful learning process is needed. One of them is Tajwid Putar, a media created by Jeni Agustina Suyanto, a teacher of MAN 1 Lubuklinggau, South Sumatra. According to her, TPQ Ar-Risalah is the only educational institution in East Java that used Tajwid Putar. The objectives of this study were to describe the Tajwid learning process by implementing Tajwid Putar, the students’ interest in learning in Tajwid using Tajwid Putar, and the learning achievement in Tajwid using Tajwid Putar. This study used a qualitative approach. The data was collected by interview, observation and documents, which were then analyzed by using an interactive model of Miles and Huberman. The result suggested that the learning process of Tajwid which employed the Tajwid Putar has been effectively made students to be more active, interactive and festive, so that they quickly understood Tajwid and was able to recite the Koran well. Students’ enthusiasm was increased in learning Tajwid compared to the use of conventional methods. The students' learning achievement was also shown to be increased, which could be measured by the score of the test contained within the student report book